Comparative Study of Procedural Text Writing Skills of Grades 4 and 6 Students at SD Al Hikmah Surabaya - Bambang, Bambang; Wasino, Wasino; Bashori, Muzakki (Proceedings of International Conference on Science, Education, and Technology, 2025)
Writing skills are one of the basic competencies that must be mastered by students, especially in the context of writing procedural texts. Writing procedural texts involves the ability to devise clear and structured steps in completing a task or activity. At the basic education level, this skill is very important because it helps students in understanding and organizing information systematically. This study aims to analyze the differences in procedural writing skills between 4th and 6th grade students at SD Al Hikmah Surabaya. The reason for choosing grade 4 and grade 6 as the object of research is because the two levels have the same learning topic, namely writing procedural texts. This study uses a quantitative method with a descriptive approach, where data is collected through procedural writing tasks given to 4th and 6th grade students. This assignment requires students to write down procedures related to daily activities such as how to make food or how to clean tools. The results showed that grade 6 students had better ability to write procedural texts compared to grade 4 students, especially in terms of clarity of steps, use of appropriate language, and the ability to explain the details of the procedure. This difference can be influenced by age factors, learning experience, and the level of cognitive understanding of students. This research is expected to provide insight for teachers in designing more effective learning to improve students' procedural writing skills at the elementary level.